Water remediation using calcium phosphate derived from marine residues - Eduardo A. Borges da Silva (2012)
The processing of natural resources in marine and freshwater ecosystems, directly operated by industries related to maritime sector, contributes annually to several million tons of waste. The reuse and economic recovery of this waste would be very desirable and profitable, either economically or environmentally. In this work, the remediation of hazardous divalent metal ions from aqueous solutions using biological apatites derived from marine residues was addressed. The biological apatite (calcium phosphate particles) was produced by heat treatment of fish bones. Experimental sorption studies of kinetics and equilibrium of the metal ions as well as an evaluation of competitive sorption behavior for lead immobilization were carried out in batch operation mode. The efficiency and mechanisms of lead sorption on two different particle sizes of calcium phosphate from aqueous solution were investigated. The results showed a high adsorption capacity of the biosorbent for Pb2+ (above 370 mg/g(ads.)), in opposition to Cd2+ and Zn2+. For the case of low initial concentrations of the metal ion, reducing the biosorbent particles size increases the sorption rate. It was possible to verify that lead immobilization proceeds with a rapid surface complexation of the lead on the sorption sites before partial dissolution of calcium phosphate and formation of pyromorphite-like compounds. By the selectivity experiments, performed using binary systems-Pb/Cd and Pb/Zn-it was evidenced a competitive process between the divalent ions, which leads to a considerable decrease on the adsorption capacity of the adsorbent material for all the metals.